Tinjauan Hukum Islam Terhadap Sistem Kerjasama Antara Agen dan Penjual Mainan Di Desa Kranggan Kecamatan Sukorejo Kabupaten Ponorogo - Amir Mukminin (Lisyabab : Jurnal Studi Islam dan Sosial, 2020)
The purpose of this study was conducted to determine the review of Islamic law on cooperation agreements between agents and toy sellers, to find out Islamic legal review of cooperative capital between agents and toy sellers, to find out Islamic legal review of profit sharing between agents and toy sellers in the village of Kranggan District Sukorejo Ponorogo Regency. According to the type of this research including qualitative research in the field means finding data to the field directly, with a normative approach. While data collection techniques use interviews, observation, and documentation. Data processing techniques are editing, organizing, and research findings, and data analysis techniques are using deductive methods. The results of this study can be concluded that the implementation of the contract in the system of cooperation between agents and toy sellers is not contrary to Islamic law. Because the contract has fulfilled the harmony and the requirements of the shirkah ‘inan. regarding the capital system is legal, because the capital system in shirkah ‘inan there is no requirement that the business capital must be the same amount, and also not required to bear the same risk. And regarding the distribution of profits according to the Shirkah contract where the profits and losses come from the amount of capital issued even though the percentage level has not been determined at the beginning, because it has become a habit and there are no parties harmed.